I will ruin you : a novel [large type] - Barclay, Linwood (Harper Large Print, an imprint of HarperCollins Publishers, 2024)
"In the latest novel from New York Times bestselling author Linwood Barclay, a teacher's act of heroism inadvertently makes him the target of a dangerous blackmailer who will stop at nothing to get what he wants. How would you react in a life-or-death situation? It's a question everyone asks themselves, but few have to face in real life. English teacher Richard Boyle certainly never thought he would find himself talking down a former student intent on harming others, but when Mark LeDrew shows up at Richard's school with a bomb strapped to his chest, Richard immediately jumps into action. Thanks to some quick thinking, he averts a major tragedy and is hailed as a hero, but not all the attention focused on him is positive. Richard's brief moment in the spotlight puts him in the sights of a deranged blackmailer with a score to settle. The situation rapidly spirals out of control, drawing Richard into a fraught web of salacious accusations and deadly secrets. As he tries to uncover the truth he discovers that there's something deeply wrong in the town--something that ties together Mark, the blackmailer, and a gang of ruthless drug dealers, and Richard has landed smack in the middle of it. He's desperate to find a way out, but everyone in his life seems to be hiding something, and trusting the wrong person could cost him everything he loves. What price will he pay for one good deed?"--